Predictors of Responsiveness to GLP-1 Receptor Agonists in Insulin-Treated Patients with Type 2 Diabetes - Colleen Gavigan; Thomas Donner (Journal of Diabetes Research)
Background. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are potent antihyperglycemic agents with beneficial effects on weight, cardiovascular, and renal outcomes. Physicians lack guidance as to which patients with insulin-requiring type 2 diabetes will respond best to GLP-1 RAs with respect to glycemic control, insulin dose reduction, and weight loss. This study evaluated the efficacy of GLP-1 RAs in patients with type 2 diabetes on insulin and patient factors that may predict a beneficial clinical response. Methods. Adults with type 2 diabetes treated with insulin who had a GLP-1 RA added to their regimen were evaluated retrospectively. Baseline parameters and outcomes at 3, 6, and 12 months were collected. Results. Among the 81 patients included, there was a mean reduction in hemoglobin A1C of 0.94% (SD, 0.26; p=0.0007), 0.40% (SD, 0.21; p=0.0636), and 0.58% (SD, 0.23, p=0.0154) at 3, 6, and 12 months, respectively, following the addition of a GLP-1 RA. There was also a reduction in body weight noted at each time point. Baseline characteristics including BMI, duration of diabetes, and insulin requirement did not significantly affect A1C reduction when GLP-1 RA was added. At 3 months, patients with a random C-peptide that was normal (≥0.8 ng/ml) were significantly more likely to have discontinued insulin than those with random C-peptide that was low (<0.8 ng/ml) (11 of 23 vs. 0 of 7 patients, p=0.029). Conclusions. The addition of a GLP-1 RA reduced HbA1C, weight, and insulin requirements in this cohort of patients with type 2 diabetes on insulin. BMI, baseline insulin dose, and diabetes duration did not predict response. A C-peptide level≥0.8 ng/ml predicted a beneficial response after 3 months of therapy.